PENGARUH PROYEK ZERO WASTE SCHOOL TERHADAP KESADARAN BERKELANJUTAN DAN KETERAMPILAN BERPIKIR KRITIS SISWA SMA - Fildza Huaina Arrifa, - (2021)
The zero waste school project is one of the learning activities in order to shape the character of students' awareness of sustainable issues and train critical thinking skills so that students are able to make decisions correctly and responsibly in realizing SDG's goals. The purpose of this study was to identify the effect of zero waste school project learning on sustainability consciousness and students' critical thinking skills. This research uses Quasy Experimental method with Non-Equivalent Control Group Design. The sample consisted of 63 students in the experimental class and 63 students in the control class. In the implementation of learning in the experimental class using the zero waste school project model and in the control class using the conventional model. Research data were collected using a sustainability consciousness questionnaire and description tests given before and after the learning was carried out. Based on further tests showed that the zero waste school project can affect the sustainability consciousness and critical thinking skills of students higher than the learning provided without the project. This learning motivates students to learn independently by finding their own information from various sources, such as a team of experts, the environment, the media and the internet so that students are more sensitive to sustainable issues. This learning also trains students to think critically about contextual issues related to sustainable development.